2022
DOI: 10.1177/17455057221118170
|View full text |Cite
|
Sign up to set email alerts
|

Unintended pregnancy and associated factors during COVID-19 pandemic in Ethiopia: Community-based cross-sectional study

Abstract: Introduction: The term ‘unintended pregnancy’ refers to a pregnancy that occurred when no children were desired or occurred earlier than desired. Unintended births account for one out of every three births in Ethiopia, and they are the leading cause of maternal morbidity and mortality. During the coronavirus disease (COVID-19) pandemic, this could be useful. COVID-19 has a significant impact on maternal health care utilization, including family planning services. As a result, this study aimed to assess uninten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 55 publications
1
6
0
Order By: Relevance
“… 10 Sexual and reproductive services were much harder to come by during COVID-19, leaving women and adolescent girls in particular less able to control their fertility. 12 Our results are remarkably similar to other studies conducted in Ethiopia, 8 and Uganda. 9 This result gives insight to policymakers and stakeholders to establish management strategies for adolescent girls to prevent unintended pregnancy in any similar crisis.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“… 10 Sexual and reproductive services were much harder to come by during COVID-19, leaving women and adolescent girls in particular less able to control their fertility. 12 Our results are remarkably similar to other studies conducted in Ethiopia, 8 and Uganda. 9 This result gives insight to policymakers and stakeholders to establish management strategies for adolescent girls to prevent unintended pregnancy in any similar crisis.…”
Section: Discussionsupporting
confidence: 89%
“… 7 These unwanted pregnancies predominately happen in the sub-Saharan Africa region. 8 The COVID-19 pandemic worsened teenage girls’ vulnerability to unwanted pregnancies. 9 COVID-19 limited women’s access to contraceptives and other sexual and reproductive health services.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An unwanted pregnancy negatively affects reproductive health, decreases a women’s quality of life, and diminishes workforce productivity. 12 Findings of a study showed that 36.6% of unintended pregnancies in women were linked to the COVID-19 pandemic, 13 with a higher magnitude (47.17%) of unintended pregnancies in women who were not autonomous to decide on the use of family planning. 14 …”
Section: Introductionmentioning
confidence: 99%